INSTRUCTIONAL LEADERSHIP: AN ISLAMIC PERSPECTIVE - Muhammad Hatta (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2014)
This paper discusses descriptively the instructional leadership from an Islamic perspective. It also attempts to review the literature pertinent to the instructional leadership and to discuss the concepts and roles of the principal as an instructional leader and their tasks or dimensions. The effective instructional education characteristics comprises the education through good example, education through norms, education through advise and counselling, education through observation and supervision and education through rewards and punishment also discussed in the paper. The paper identified that the leadership model of Mohamad Johdi and Bakare (2009) is an applicable model of Islamic instructional LEADERSHIP (L-Leader, E-Educational, A-Aim, D-Delivery, E-Empowerment, R-Robust, S-Style, H-Humble, P-Piety), and I-Intelligent. The leader with the Imam concept is the one who is supposed to be obeyed by the followers